2022
DOI: 10.3390/pharmaceutics14071379
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of Autophagy-Inducing Particles for the Treatment of Abnormal Lipid Accumulation

Abstract: Autophagy is a fundamental housekeeping process by which cells degrade their components to maintain homeostasis. Defects in autophagy have been associated with aging, neurodegeneration and metabolic diseases. Non-alcoholic fatty liver diseases (NAFLDs) are characterized by hepatic fat accumulation with or without inflammation. No treatment for NAFLDs is currently available, but autophagy induction has been proposed as a promising therapeutic strategy. Here, we aimed to design autophagy-inducing particles, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…These are molecules that specifically target a known protein involved in the autophagy pathway. One such molecule is Tat-beclin 1 (Tat-BECN1), a peptide known to stimulate autophagy through mobilization of endogenous Beclin 1 [ 95 ]. Other molecules in this class of drugs are TFEB activators [ 96 ] and ULK1 activators [ 97 ], but their role in regulating hepatic lipotoxicity remains to be investigated.…”
Section: Pharmacological and Nonpharmacological Inducers Of Autophagy...mentioning
confidence: 99%
“…These are molecules that specifically target a known protein involved in the autophagy pathway. One such molecule is Tat-beclin 1 (Tat-BECN1), a peptide known to stimulate autophagy through mobilization of endogenous Beclin 1 [ 95 ]. Other molecules in this class of drugs are TFEB activators [ 96 ] and ULK1 activators [ 97 ], but their role in regulating hepatic lipotoxicity remains to be investigated.…”
Section: Pharmacological and Nonpharmacological Inducers Of Autophagy...mentioning
confidence: 99%
“…Previous studies mainly focused on pericytes and RPE cells' autophagy in DR. Wang et al (17) found that the high expression of the autophagy-related gene (ARG) MAPK3 in retinal pigment epithelial cells might be involved in outer bloodretina barrier destruction in DR. Lin et al (18) described in detail the effect of oxidative stress-activated autophagy on RGCs; however, it remains controversial whether the autophagy in RGCs is beneficial. It is worth noting that there is increasing evidence that autophagy is related to senescence, another common pathological change in endocrine and neurological diseases (19)(20)(21). Conclusively, the role of the double-edged sword of autophagy in DR is complicated; particularly significant is that the role and mechanism of RGCs autophagy in hyperglycemia and DR remain unclear.…”
Section: Introductionmentioning
confidence: 99%